Parasitic Infections: Etiology, Epidemiology, Pathogenesis, and Diagnosis (Eurasian Medical Research Periodical, 2026)
Parasitic infections are diseases caused by protozoa, helminths, and ectoparasites that can affect the internal organs, blood, nervous system, and skin of the human body. [1] These infections remain a significant public health concern worldwide, particularly in developing countries. [1,10] This article provides a scientific review of their etiology, global epidemiology, pathogenesis, clinical manifestations, diagnostic approaches, treatment, and prevention strategies. Special attention is given to modern laboratory, serological, and molecular diagnostic methods, including Polymerase Chain Reaction (PCR) and Enzyme-Linked Immunosorbent Assay (ELISA)